Notice of Retraction: Implement embedded controller using FPGA chip - Haresh Pandya; Mahesh Rangapariya; Jitendra Rajput (International Journal of Reconfigurable and Embedded Systems (IJRES), 2019)
This article has been retracted by the publisher.Notes: Notice of Retraction: After careful and considered review of the content of this paper by a duly constituted expert committee, this paper has been found to be in violation of IAES's Publication Principles. We hereby retract the content of this paper. Reasonable effort should be made to remove references to this paper. The presenting author of this paper has the option to appeal this decision by contacting info@iaesjournal.com.------------------------------------The designer of an FPGA embedded processor system has complete flexibility to select any combination of peripherals and controllers. In fact, the designer can invent new, unique peripherals that can be connected directly to the processor bus. If a designer has a non-standard requirement for a peripheral set, this can be met easily with an FPGA embedded processor system. For example, a designer would not easily find an off-the-shelf processor with ten UARTs. However, in an FPGA, this configuration is very easily accomplished.